PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SEKOLAH DASAR - Ghiska Sheva Reisha Putri; Yeni Dwi Kurino; Ujiati Cahyaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Discovery Learning model on the mathematical problem-solving ability of elementary school students, specifically on the topic of currency and daily financial transactions. The method used in this research was a quantitative approach with a quasi-experimental design, specifically the nonequivalent control group design. The study was conducted at SDN Kadipaten V, Majalengka Regency, involving 42 fourth-grade students as the sample, divided into an experimental class (IV-A, n = 21) utilizing Discovery Learning and a control class (IV-B, n = 21) utilizing direct instruction. Data were collected using essay test instruments measuring four problem-solving indicators based on Polya's framework: understanding the problem, devising a plan, carrying out the plan, and looking back. Data analysis techniques included descriptive statistics, Paired Sample t-test, Independent Sample t-test, and Cohen's d effect size calculation. The results showed a significant increase in the experimental group's mean score from a pretest of 62.38 to a posttest of 80.95 (p = 0.000 < 0.05). Furthermore, the Independent Sample t-test revealed a significant difference between the experimental posttest mean (80.95) and the control posttest mean (70.71) with p = 0.001. The effect size calculation yielded a Cohen's d value of 1.573, which falls into the large effect category (d > 0.80). It can be concluded that the implementation of the Discovery Learning model significantly enhances elementary students' mathematical problem-solving skills and serves as an effective learning strategy.